PREPARATION OF DFA III FROM DAHLIA (DAHLIA sp.) TUBERS BY NONOMURAEA sp. INULIN FRUCTOTRANSFERASE - pudjiraharti, sri (Teknologi Indonesia, 2016)
A functional oligosaccharide Difructose anhydride III (DFA III) can be made enzymatically from inulin. Inthis research, tubers of Dahlia plant (Dahlia sp.), which is known as one of the sources of inulin, was processedinto chips form and utilized for DFA III preparation using Nonomuraea sp. Inulin fructotransferase (IFTase). Priorto drying process, Dahlia tubers were blanched first at different blanching times (5, 10, 15, 20, and 25 minutes) tofind out the optimum time to produce white and clear chips. To study the influence of IFTase concentrations andreaction time on DFA III production, 10 g of Dahlia chips were reacted with different concentrations of enzyme35, 70, 140, 210, 280 U in 200 ml reaction mixture and incubated at different periods of time (3, 6, 9 and 12hours). DFA III produced was measured by High Performance Liquid Chromatography (HPLC) method. The resultindicated that blanching in boiling water for 15 minutes resulted in chips with clear and white color. It was alsoobserved, the higher the amount of enzyme used and the longer the incubation period, the higher the concentrationof DFA III resulted. Statistical analysis using single-factor Anova and t-test for P=0.05 showed that reaction forDFA III production using enzyme concentration of 35 U was significantly different from that using 140, 120, and280 U; reaction using enzyme concentration of 210 was significantly different from that of 280 U. However, DFAIII production using enzyme concentration of 35 U was more effective than using the higher one. DFA III of 0.83g was produced using enzyme amount of 35 U, while 1.45 g DFA III produced using 280 U can increase DFA IIIpercentage up to 73.86%.